2012
DOI: 10.1007/s10904-011-9609-0
|View full text |Cite
|
Sign up to set email alerts
|

Well-Dispersed Fe3O4/SiO2 Nanoparticles Synthesized by a Mechanical Stirring and Ultrasonication Assisted Stöber Method

Abstract: Core-shell structured Fe 3 O 4 /SiO 2 nanoparticles (NPs) sized 40-50 nm with a narrow size distribution have been synthesized by a mechanical stirring and ultrasonication assisted Stöber method at the room temperature. It is shown that the combination of the ultrasonication and mechanical stirring during the preparation process benefits the formation of the well-dispersed NPs. The Fe 3 O 4 /SiO 2 core-shell microstructure is identified with X-ray diffraction and transmission electron microscopy measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It has been shown also that coating of magnetic particles with non-magnetic materials such as silica influences the value of magnetization due to the quenching of surface moments [28]. The thicker silica shell-the lower the saturation magnetization [8]. Barick et al [22] reported on the preparation of dispersed iron oxide Fe 2 O 3 nanoparticles in silica matrix using sol-gel process.…”
Section: Magnetization Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown also that coating of magnetic particles with non-magnetic materials such as silica influences the value of magnetization due to the quenching of surface moments [28]. The thicker silica shell-the lower the saturation magnetization [8]. Barick et al [22] reported on the preparation of dispersed iron oxide Fe 2 O 3 nanoparticles in silica matrix using sol-gel process.…”
Section: Magnetization Measurementsmentioning
confidence: 99%
“…Variety of the inorganic and polymeric materials has been reported as possible carriers for magnetic materials. Among them silica, an inorganic carrier, seems to be interesting supporting material, which can be easily prepared and retains stability in most chemical and biological environments [7,8]. It has been demonstrated that the formation of a passive coating of inert materials such as silica on the surfaces of iron oxide nanoparticles could help to prevent their aggregation in liquids and improve their chemical stability [9].…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification was aiming to overcome the colloidal instability of Fe 3 O 4 NPs induced by the magnetic dipole interaction and their inherently large surface energy. [21][22][23] Previously we have succeeded in the synthesis of 3-55 aminopropyltriethoxysilane (APTS)-and polyethyleneimine (PEI)-coated Fe 3 O 4 NPs via a one-pot hydrothermal approach. 24,25 The dense primary amine groups on the surface of Fe 3 O 4 NPs rendered by the APTS or PEI coating not only endow the NPs with colloidal stability, but also mediates convenient modification 60 and functionalization of the particle surfaces for various biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, tremendous investigations have also been performed in magnetic Fe 3 O 4 nanoparticles . The preparation methods for Fe 3 O 4 nanocarriers include coprecipitation, ultrasonic precipitation, sol‐gel, microemulsions, hydrothermal methods, and etc.…”
Section: Anticancer Drug Delivery Systems Based On Inorganic Nanocarrmentioning
confidence: 99%
“…Magnetic nanoparticles are attractive to researchers from different disciplines, including catalysis, data storage, and magnetic separation. Currently, due to their promising biocompatibility, Fe 3 O 4 nanoparticles are also commonly used in biological applications such as magnetic resonance imaging (MRI), cell labeling, and cancer treatment . When used in biological systems, Fe 3 O 4 nanoparticles require proper surface coating or other protection strategies to keep their stability, because the nanoparticles display high chemical activity and could be easily oxidized.…”
Section: Anticancer Drug Delivery Systems Based On Inorganic Nanocarrmentioning
confidence: 99%